(untitled) (Journal of Civil Engineering Researchers, 2020)
Structural control systems are used to reduce structural damage in earthquakes. These systems have developed significantly over the last few decades. They can be broadly classified into three categories: 1) Passive control system in which structures are equipped with devices that do not require an external energy source. 2) Active control systems in which the structures are equipped with processing and transmission sensors and in which there are devices that need an external energy source to work, and 3) Semi-active control system to change There are structural properties that require little external energy. In the present review article, we have tried to fully evaluate this field of study by evaluating four valid articles in the field of evaluating the effects of energy consuming dampers in steel frames. The results of the studies showed that the presence of various dampers including new submersible metal dampers, hybrid, viscoelastic, submersible strip wave and two-level submersible torque has caused the performance indicators of the steel frame, including; Shear strength, displacement of structural floors, energy, hysterical performance (hysteresis curve), etc., which indicates the performance of the structure, has been improved and in all evaluated indicators, the structure has increased the level of performance.